Печать
Просмотров: 9
Звезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активна
 
\begin{equation} 1)f(0)=e^{-2.0}=e^{0}=1; \end{equation} \begin{equation} {f}'(x)=e^{-2x}*(-2)=-2e^{-2x}; \end{equation} \begin{equation} {f}'(0)=-2e^{-3.0}=-2; \end{equation} \begin{equation} y=1+(-2)(x-0);y=1-2x; \end{equation} \begin{equation} 2)f(0)=e^{0}+ \sin 0=1+0=1; \end{equation} \begin{equation} {f}'(x)=e^{x}+ \cos x; \end{equation} \begin{equation} {f}'(0)=e^{0}+ \cos 0=1+1=2; \end{equation} \begin{equation} y=1+2(x-0);y=2x+1; \end{equation} \begin{equation} 3)f(1)=1*2=2; \end{equation} \begin{equation} {f}'(x)=2^{x}+x*2^{x} \ln 2=2^{x}(1+ \ln 2*x); \end{equation} \begin{equation} {f}'(1)=2(1+ \ln 2*1)=2+2 \ln 2; \end{equation} \begin{equation} y=2+(2+2 \ln 2)(x-1); \end{equation} \begin{equation} y=2+2x-2+2x \ln 2-2 \ln 2; \end{equation} \begin{equation} y=2x(1- \ln 2)-2 \ln 2; \end{equation} \begin{equation} f(1)=3*1+ \ln 1=3+0=3; \end{equation} \begin{equation} {f}'(x)=3+\frac{1}{x}; {f}'(1)=3+\frac{1}{1}=4; \end{equation} \begin{equation} y=3+4(x-1);y=4x-1; \end{equation}